PERANAN PEREMPUAN DALAM PERPEKTIF HUKUM ISLAM - Saputro, Eko Andy (Jurnal al Hikmah, 2017)
The Quran recognizes the role of men and women as individuals and as members of society. The Emancipation of women is an affair always in the heart of the Prophet. The Quran gives the right of inheritance and divorce to women, centuries before Western women are declared eligible for that status. The Quran also establishes the social norms of the new community. A very basic revolutionary step. The women of the first people in Medina took full part in their public life, and some, according to Arab custom, fought on the side of men in battle. They do not feel Islam as a pressing religion. This article attempts to examine the role and position of women in Islam, judging by her position as an individual, a partner of her husband, and part of society. Keywords: womenâs role, emancipation, gender, shariâa.